2022
DOI: 10.1111/ddi.13529
|View full text |Cite
|
Sign up to set email alerts
|

Energy and physiological tolerance explain multi‐trophic soil diversity in temperate mountains

Abstract: Aim Although soil biodiversity is extremely rich and spatially variable, both in terms of species and trophic groups, we still know little about its main drivers. Here, we contrast four long‐standing hypotheses to explain the spatial variation of soil multi‐trophic diversity: energy, physiological tolerance, habitat heterogeneity and resource heterogeneity. Location French Alps. Methods We built on a large‐scale observatory across the French Alps (Orchamp) made of seventeen elevational gradients (~90 plots) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 134 publications
0
14
0
Order By: Relevance
“…Large trait databases have the potential to address this trade-off between feasibility and completeness. By supporting the assignment of species (or higher taxonomic ranks) to trophic and/or functional groups, they reduce the dimensionality of ecological communities without biasing studies toward a single trophic level or taxonomic group [30, 15]. Yet, challenges remain: although we have trait databases available for some of them, our trait knowledge is limited for most groups of soil organisms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large trait databases have the potential to address this trade-off between feasibility and completeness. By supporting the assignment of species (or higher taxonomic ranks) to trophic and/or functional groups, they reduce the dimensionality of ecological communities without biasing studies toward a single trophic level or taxonomic group [30, 15]. Yet, challenges remain: although we have trait databases available for some of them, our trait knowledge is limited for most groups of soil organisms.…”
Section: Methodsmentioning
confidence: 99%
“…The difficulty of integrating data distributed across heterogeneous sources remains. As a result, integrative analyses of soil communities that span several taxonomic groups and integrate multitrophic interactions are scarce — see [15] for an example — although essential to improve our understanding of the links between soil biodiversity and ecosystem functioning [16].…”
Section: Introductionmentioning
confidence: 99%
“…(Bloor, Si-Moussi, Taberlet, Carrère, & Hedde, 2021;Calderón-Sanou et al, 2022;Guerrieri et al, 2022). This approach has the advantage of providing a reasonable representation of biodiversity, with good information on selected key taxa and few taxa completely missing, and might thus allow exploring complex relationships between multiple taxonomic groups (Bloor et al, 2021;Calderón-Sanou et al, 2022). Nevertheless, similarly to approach 2.1, it remains costly and labor-intensive.…”
Section: Combining Very Generalist and More Specific Primersmentioning
confidence: 99%
“…One decade of advances on eDNA metabarcoding has fostered our ability to obtain biodiversity data, filling long-standing gaps on many components of both terrestrial and aquatic environments. Nevertheless, just a few studies have taken the challenge of attempting analyses covering multiple taxonomic groups, and trying to identify the complex multi-trophic interactions between them (but see Bloor et al, 2021;Calderón-Sanou et al, 2021;Calderón-Sanou et al, 2022;Martinez-Almoyna et al, 2019). Several approaches can now allow an all-inclusive community ecology, potentially allowing unprecedented understanding of patterns and processes underlying biodiversity variation, but both technical and conceptual developments will be required for a more widespread application of the all-inclusive ecology, and some challenges are shared by most approaches.…”
Section: Conclusion: Challenges and Opportunities For An All-inclusiv...mentioning
confidence: 99%
“…Moving up from single taxa to multi‐trophic assemblages, Calderón‐Sanou et al (2022) tested the role of energy, physiological tolerance, habitat heterogeneity and resource heterogeneity on the spatial variation of soil multi‐trophic diversity across the French Alps. Using an environmentally stratified sampling design together with soil environmental DNA and a machine learning algorithm, the authors found the strongest support for the energy and physiological tolerance hypotheses across the 36 analysed soil trophic groups, while the other two hypotheses were important only for some specific ones.…”
Section: This Issuementioning
confidence: 99%